Lattice defect engineering advances n-type PbSe thermoelectrics - Qian Deng; Xiao-Lei Shi; Meng Li; Xiaobo Tan; Ruiheng Li; Chen Wang; Yue Chen; Hongliang Dong; Ran Ang; Zhi-Gang Chen (Nature Communications)
Abstract Te-free thermoelectrics have garnered significant interest due to their immense thermoelectric potential and low cost. However, most Te-free thermoelectrics have relatively low performance because of the strong electrical and thermal transport conflicts and unsatisfactory compatibility of interfaces between device materials. Here, we develop lattice defect engineering through Cu doping to realize a record-high figure of merit of ~1.9 in n-type polycrystalline PbSe. Detailed micro/nanostructural characterizations and first-principles calculations demonstrate that Cu-induced interstitial defects and nanoprecipitates simultaneously optimize electron and phonon transport properties. Moreover, a robust Co/PbSe interface is designed to effectively prevent chemical reactions/diffusion; this interface exhibited a low electrical contact resistivity of ~10.9 μΩ cm2, excellent durability, and good stability in the thermoelectric module, which achieves a record-high conversion efficiency of 13.1% at a temperature difference of 460 K in segmented thermoelectric modules. This study lays the groundwork for advancing the development of Te-free selenide-based thermoelectric materials.